Influence of Socio-Economic Adversity on Personal Security In Kilifi County, Kenya - Katana, Leonard (European Journal of Applied Sciences, 2022)
Personal security is an important component of human security. Prior studies have established a relationship between socioeconomic adversities and personal security. However, there is little knowledge on the influence of social-economic adversities on the personal security of individuals of Kilifi County in Kenya. The objective of the study was to determine whether socioeconomic adversity has an impact on the personal security of people in Kilifi County. The study used general strain theory as the basis for evaluating the influence of socio-economic adversity on personal security. Quantitative data were analyzed using descriptive statistics while qualitative data was analyzed thematically. The study found that 74.06% of the Kilifi County residents have compromised personal security; 63.82% of the residents attributed compromised personal security to low income and unavailability of employment opportunities. The study recommends the deliberate measures by local government, national government, and development partners to provide means of sustainable livelihood and employment opportunities as a sustainable solution to personal security.